C-EBPβ mediates in cigarette/IL-17A-induced bronchial epithelial–mesenchymal transition in COPD mice - Shuyuan Chu; Libing Ma; Yashan Wu; Xiaoli Zhao; Bo Xiao; Qilu Pan (BMC Pulmonary Medicine, 2021)
Abstract Background Cigarettes smoking and IL-17A contribute to chronic obstructive pulmonary disease (COPD), and have synergistical effect on bronchial epithelial cell proliferation. CCAAT/enhancer-binding protein β (C-EBPβ) could be induced by IL-17A and is up-regulated in COPD. We explored the effect of cigarettes and IL-17 on bronchial epithelial–mesenchymal transition (EMT) in COPD mice and potential mechanism involved with C-EBPβ in this study. Methods COPD model was established with mice by exposing to cigarettes. E-Cadherin, Vimentin, IL-17A and C-EBPβ distributions were detected in lung tissues. Primary bronchial epithelial cells were separated from health mice and cocultured with cigarette smoke extract (CSE) or/and IL-17A. E-Cadherin, Vimentin and IL-17 receptor (IL-17R) expressions in vitro were assessed. When C-EBPβ were silenced by siRNA in cells, E-Cadherin, Vimentin and C-EBPβ expressions were detected. Results E-Cadherin distribution was less and Vimentin distribution was more in bronchus of COPD mice than controls. IL-17A and C-EBPβ expressions were higher in lung tissues of COPD mice than controls. In vitro, C-EBPβ protein expression was highest in CSE + IL-17A group, followed by CSE and IL-17A groups. E-cadherin expression in vitro was lowest and Vimentin expression was highest in CSE + IL-17A group, followed by CSE or IL-17A group. Those could be inhibited by C-EBPβ silenced. Conclusions C-EBPβ mediates in cigarette/IL-17A-induced bronchial EMT in COPD mice. Our findings contribute to a better understanding on the progress from COPD to lung cancers, which will provide novel avenues in preventing tumorigenesis of airway in the context of cigarette smoking.